2015 IEEE 13th International Conference on Industrial Informatics (INDIN) 2015
DOI: 10.1109/indin.2015.7281836
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and comparative study of using a CNC machine spindle motor power and infrared technology for the design of a cutting tool condition monitoring system

Abstract: Abstract-This paper outlines a comparative study to compare between using the power of the spindle and the infrared images of the cutting tool to design a condition monitoring system. This paper compares the two technologies for the development of a tool condition monitoring for milling processes. Wavelet analysis is used to process the power signal. Image gradient and Wavelet analyses are used to process the infrared images. The results show that the image gradient and wavelet analysis are powerful image proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Many scholars have conducted numerous explorations on tool wear conditions monitoring technology using power signals. In the feature extraction method, Elgargni and Al-Habaibeh (2015) used discrete wavelet transformation (DWT) to extract the features of the collected power signals and found that the approximate coefficient curve of the normal tool gradually shifted to the left compared with the worn tool, which can clearly distinguish the tool wear conditions. As for the model establishment method, Rodrigo da Silva et al (2016) collected acoustic emission signals and power signals as samples and used a probabilistic neural network to establish a tool wear conditions monitoring model to identify the tool wear conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have conducted numerous explorations on tool wear conditions monitoring technology using power signals. In the feature extraction method, Elgargni and Al-Habaibeh (2015) used discrete wavelet transformation (DWT) to extract the features of the collected power signals and found that the approximate coefficient curve of the normal tool gradually shifted to the left compared with the worn tool, which can clearly distinguish the tool wear conditions. As for the model establishment method, Rodrigo da Silva et al (2016) collected acoustic emission signals and power signals as samples and used a probabilistic neural network to establish a tool wear conditions monitoring model to identify the tool wear conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The vibration and power signals are used as input to determine the condition of the cutting tool when used with materials that are difficult to process. Elgargni and Al-Habaibeh [7] also use wavelet analysis to process infrared images and the power of the spindle and recognize the condition of cutting tool. Therefore, the wavelet analysis is a technique widely used in monitoring the condition of cutting tool.…”
Section: Introductionmentioning
confidence: 99%